Human Fertility Methods and Protocols - Rosenwaks, Zev.; Wassarman, Paul M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Human Fertility: Methods and Protocols is intended for all practitioners of reproductive medicine and ART, as well as for embryologists and reproductive, developmental, cell, and molecular biologists, and others in the biomedical sciences. The volume presents straight-forward manner best practice approaches for overcoming a host of fertility challenges.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.     Authoritative and cutting-edge, Human Fertility: Methods and Protocols aids scientists in continuing to study assisted reproductive technologies.
General Aspects of Fertility and Infertility -- Genetics of Male Fertility -- Genetics of Female Infertility due to Anomalies of the Ovary and Mullerian Ducts -- Gene Polymorphisms in Female Reproduction -- Understanding the Spermatozoon -- Derivation of Human Embryonic Stem Cells (hESC) -- The Endocrinology of the Menstrual Cycle -- Assisted Reproductive Techniques -- Novel Markers of Male Infertility -- Luteal Phase Support in ART Treatments -- General Principles of Cryopreservation -- In Vitro Maturation of Immature Human Oocytes for Clinical Application -- GnRH Antagonist Based Protocols for In Vitro Fertilization -- Ovarian Stimulation for IVF: Mild Approaches -- IVF Stimulation: Protocols for Poor Responders -- Oocyte Retrieval and Quality Evaluation -- Sperm Retrieval and Quality Evaluation -- Treatment of Male Infertility -- Techniques for Slow Cryopreservation of Embryos -- Cryopreservation of Eggs -- Ovarian Tissue Cryopreservation and Transplantation. A Realistic, Effective Technology for Fertility Preservation -- Detection of Monogenic Disorders and Chromosome Aberrations by Preimplantation Genetic Diagnosis -- Embryo Culture and Selection: Morphological Criteria -- Embryo Selection using Metabolomics -- Embryo Transfer -- Safety of Assisted Reproductive Technologies -- Human Germ Cell Differentiation from Pluripotent Embryonic Stem Cells and Induced Pluripotent Stem Cells.
Keywords: Cell biology; Embryology; Developmental biology; Cell Biology; Embryology; Developmental Biology